Assessment of foreign body sensation and patient satisfaction after inguinal hernia repair: A prospective randomized comparative study. - Nanda, Yashaswini; Mrigesh, Kumar; Jumde, Suvit; Tanu Pradhan (Student's Journal of Health Research Africa, 2025)
Background Lichtenstein tension-free mesh repair is the standard approach for inguinal hernia. However, patient-centered outcomes such as postoperative pain and foreign body sensation (FBS) influence long-term satisfaction. Lightweight meshes have been developed to reduce stiffness and mesh awareness. This study compared lightweight and heavyweight polypropylene meshes regarding FBS and inferred patient satisfaction. Methods This prospective randomized comparative study was conducted at Acharya Vinoba Bhave Rural Hospital (AVBRH), a 1200-bed tertiary-care teaching hospital in Wardha, India, from September 2016 to September 2018. One hundred adult male patients with unilateral, uncomplicated inguinal hernia undergoing elective Lichtenstein repair were randomized equally into heavyweight mesh (Group I) and lightweight mesh (Group II). Pain (VAS), FBS, complications, and hospital stay were recorded over 12 months. Patient satisfaction was inferred based on recovery outcomes. Results Early postoperative pain was lower in the lightweight group (mean VAS 1.98 ± 0.86 vs 2.64 ± 1.15; p<0.05). FBS was significantly higher in the heavyweight group at 1 month (24% vs 12%; χ²=4.87, p=0.027), 3 months (24% vs 8%; χ²=9.52, p=0.002), and 6 months (12% vs 4%; χ²=4.34, p=0.037). No FBS was reported in either group at 12 months. Mean hospital stay was shorter with lightweight mesh (4.78 ± 1.52 vs 6.70 ± 2.71 days). No recurrence occurred. Conclusion Lightweight polypropylene mesh significantly reduces early postoperative pain, foreign body sensation, and hospital stay without compromising recurrence rates. Recommendation Lightweight mesh should be preferred for Lichtenstein repair, especially in active and working-age patients to enhance postoperative comfort and satisfaction.